CuyBot: A Compact and Low-Cost Tracked Robot with vSLAM for Ventilation Duct Inspection - Alcoba, Marcelo Saavedra; Toconas, Brayan Duran; Palacios, Fabio Diaz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
Monitoring ventilation ducts is crucial for ensuring air quality in high-traffic spaces. However, this task presents significant challenges for cleaning staff, as the limited space and extensive length of the ducts make thorough inspection difficult. This article presents the development and evaluation of CuyBot, a compact and economical mobile robot specifically designed for the exploration and inspection of ventilation ducts. CuyBot combines manual control with semi-autonomous navigation to strategic points, optimizing its performance in complex environments. Equipped with a Lidar and integrating data from a stereo camera to generate visual odometry, the robot utilizes this information to implement Visual Simultaneous Localization and Mapping (vSLAM), enabling it to navigate and create 2D maps of the spaces. CuyBot’s capabilities were rigorously evaluated through a phased approach that included the application of vSLAM in simulated environments, testing in physical replicas of ducts, and final validation in a real ventilation duct. The results demonstrate that CuyBot navigates effectively in these challenging environments.